Collaborative Learning in Digital Environments and Student Achievement: A Cross-Sectional Quantitative Study - Zuraini Binti Idris; Halimahtul Sa’diyah Binti Mohamad; Yuliharti (Global Perspectives in Education Journal, 2026)
This study aimed to examine the relationship between collaborative learning in digital environments and student achievement among high school students in Rokan Hulu Regency. The research was conducted from January to April 2025 to investigate how digital cooperative activities are associated with educational performance and student involvement in secondary education. A quantitative cross-sectional design was used involving 176 students selected through stratified random sampling from several public high schools. Data were collected using a validated 28-item questionnaire measuring digital messaging, peer interaction, collaborative issue resolution, and knowledge sharing. Student achievement data were obtained from semester examination records and standardised assessments. The instrument demonstrated strong reliability (Cronbach’s α = .91). Data were analysed using descriptive statistics, Pearson's correlation, and multiple regression. Overall collaborative learning was significantly associated with student achievement (r = .68, p < .001). Regression analysis indicated that collaborative learning in digital environments variables were significant predictors of academic achievement (β = .57, t = 8.42, p < .001), explaining 46% of the variance (R² = .46). Peer interaction and online communication were the strongest predictors. Students actively engaged in collaborative digital learning achieved higher academic scores (M = 84.72, SD = 6.14) than less active students (M = 76.35, SD = 7.28). These results indicate that coordinated digital learning environments heighten engagement, critical thinking, and academic achievement, supporting the embedding of student-centred digital pedagogy in secondary education.